PENGARUH KEBIJAKAN DIVIDEN, LIKUIDITAS, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Adi Putra, A.A. Ngurah Dharma; Lestari, Putu Vivi (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the effect divident policy, liquidity, profitability and firm size against firm value. Firm value is an indicator of financial performance for companies that go public. High firm value would indicate strong shareholder wealth. This study was performed on companies listed in Indonesia Stock Exchange 2010-2013. The number of samples taken is 20 companies. The sampling method on this study using purposive sampling and using multiple regression analysis techniques which includes the classic assumption test and partial test (t-test) with a significant level (?) 5%. This study indicate that divident policy, liquidity, profitability and firm size partially positive effect on the firm value.
Keywords: divident policy, liquidity, profitability, firm size, firm value